Chemotherapy Induced Eosinophilia and its Significance among the Cancer Patients Treated at a Tertiary Care Teaching Hospital, West Bengal (Indian Journal of Public Health Research & Development, 2023)
AbstractBackground: Cancer is a major burden and threat to global society. It is one of the leading causes of death inboth developed and developing countries. The main modalities used for its treatment include surgery, radiation,chemotherapy, immunotherapy, and hormones.Materials & Methods: The current study was performed to find incidence of chemotherapy induced eosinopilliain patients with different cancers who were receiving standard chemotherapy regimens (minimum two cycles andmaximum six to eight cycles). Total leucocyte count, absolute eosinophil count and differential leucocyte countwas done just before starting of chemotherapy. Differential leucocyte count (DLC) was reported after 1st cycle ofchemotherapy agents, before last dose of chemotherapy, after 6 weeks of completion of chemotherapy, and aftersix month of completion of chemotherapy to see the changes on eosinophil counts.Results: Most commonly used anticancer agents were 5 FU 61 (61%), doxorubicin 43 (43%), cyclophosphomide 53(53%), cisplatin 10 (10%), paclitaxel 20 (20%), carboplatin 25 (25%), gemcitabine 11 (11%), oxaliplatin 14 (14%) andcapecitabine 11 (11%). The pre-CT eosinophil count had a mean of 3.41 (range, 2 to 4) and post-CT after 1st dosehad a mean of 5.06 (range, 3 to 8) (p
Keywords: Cancer chemotherapy, chemotherapy induced eosinophilia, drug reaction with eosinophilia and systemic symptoms (DRESS), West Bengal